2021
DOI: 10.3390/en14154686
|View full text |Cite
|
Sign up to set email alerts
|

Organic-Inorganic Novel Green Cation Exchange Membranes for Direct Methanol Fuel Cells

Abstract: Commercializing direct methanol fuel cells (DMFC) demands cost-effective cation exchange membranes. Herein, a polymeric blend is prepared from low-cost and eco-friendly polymers (i.e., iota carrageenan (IC) and polyvinyl alcohol (PVA)). Zirconium phosphate (ZrPO4) was prepared from the impregnation–calcination method and characterized by energy dispersive X-ray analysis (EDX map), X-ray diffraction analysis (XRD), Fourier transform infrared spectroscopy (FTIR), and transmission electron microscopy (TEM), then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…The methanol crossover reduces the efficiency of DMFCs by the creation of a mixed potential at the cathode. The undesired oxidation, decreasing the active sites for reduction of oxygen at the cathode, and carbon monoxide poisoning of the cathode catalyst are other methanol crossover challenges [142][143][144][145]. Nafion, as the most common PEM used in DMFCs, suf-fers from the methanol crossover despite its supreme proton conductivity and outstanding chemical, thermal, and mechanical stability [146][147][148].…”
Section: Fuel Cells 241 Membranementioning
confidence: 99%
“…The methanol crossover reduces the efficiency of DMFCs by the creation of a mixed potential at the cathode. The undesired oxidation, decreasing the active sites for reduction of oxygen at the cathode, and carbon monoxide poisoning of the cathode catalyst are other methanol crossover challenges [142][143][144][145]. Nafion, as the most common PEM used in DMFCs, suf-fers from the methanol crossover despite its supreme proton conductivity and outstanding chemical, thermal, and mechanical stability [146][147][148].…”
Section: Fuel Cells 241 Membranementioning
confidence: 99%
“…Elerian et al found that GO/ZrP generally reduces elongation and that adding ZrP particles to the polymer can alter its brittleness; whether this is a positive or negative change depends on properties like particle distribution, filler matrix adhesion, and amount of added filler 63 . In another study conducted with ZrP additive, researchers stated that with the incorporation of ZrP into the polymeric framework, the mechanical tensile strength of the membranes experienced enhancement, and this improvement stemmed from the increased compatibility among membrane components, attributed to the reinforcement of bonds ionic, hydrogen, and covalent‐between polymers and ZrP 64 . According to Abdulkarem et al, the membrane's mechanical strength improved as the amount of inorganic additive increased, and its tensile strength improved because of stress transfer from the ZrP additive to the membrane matrix 65 …”
Section: Resultsmentioning
confidence: 99%
“…However, the water uptake was too high (70.7%). Also, Gouda et al [ 121 ] chose to blend carrageenan with PVA and zirconium phosphate. Liew et al [ 122 ] modified k-carrageenan with phosphoric acid to obtain higher conductivities, thank to thehigher number of oxygen atoms in the structure.…”
Section: Green Materialsmentioning
confidence: 99%